Paraneoplastic Leser-Trélat Syndrome: Clinical Manifestations, Diagnosis and Treatment - T. A. Gaydina; A. S. Dvornikov; P. A. Skripkina (SINAPS LLC, 2022)
Examination of the skin is a widely available and simple method of examining the patient, which nevertheless allows you to diagnose systemic disorders and diseases in the human body at an early stage. A doctor of any specialty may encounter dermatological paraneoplastic syndromes in his practice, which are a group of skin diseases associated with malignant neoplasms, but not directly related to the primary tumor or its metastases. Timely analysis of dermatological paraneoplastic syndromes makes it possible to suspect malignant tumors that cause them and urgently refer the patient to an oncologist for the purpose of early diagnosis and treatment of a potentially curable oncological disease. In clinical practice, paraneoplastic Leser-Trélat syndrome is very common, which is manifested by the sudden appearance of multiple seborrheic keratomas (mainly in the back and abdomen) and an increase in their number and size over a short period of time (weeks, months). Treatment of this syndrome can be carried out both simultaneously and after treatment of the underlying malignant disease. Dermatological paraneoplastic syndromes require further in-depth study to understand the pathogenesis, create a clear classification and develop algorithms for the doctor's actions in case of their detection.